2004
DOI: 10.1007/s10147-004-0409-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of recurrence after radical surgery for nonmetastatic renal cell carcinoma

Abstract: These findings suggest that careful follow-up should be performed for patients showing a high pathological stage after radical surgery for nonmetastatic RCC, because of the higher probability of disease recurrence, and that after recurrence, intensive treatment should be considered, particularly for patients with unresectable recurrent disease occurring within 1 year after initial radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…Using these criteria the interobserver agreement was substantial, bordering on almost perfect (Cohen's kappa 0.75). The frequency of MVI found in our study is in concordance with some previous reports (6, 7, 9, 13) (17%, 42.7%, 25% and 4.7%, respectively). There is, however, considerable variation in reported frequencies of MVI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Using these criteria the interobserver agreement was substantial, bordering on almost perfect (Cohen's kappa 0.75). The frequency of MVI found in our study is in concordance with some previous reports (6, 7, 9, 13) (17%, 42.7%, 25% and 4.7%, respectively). There is, however, considerable variation in reported frequencies of MVI.…”
Section: Discussionsupporting
confidence: 93%
“…In the study by Sevinç et al, which was limited by the small population considered, CSS was not found to be significantly related to MVI (6). In our study, however, MVI turned out to be a strong independent prognosticator for organ‐confined CCRCC after RN, a finding in accordance with most of the few previous reports dealing with this issue (5, 7, 9). Our patients with MVI‐positive tumours experienced a nearly 7‐fold higher risk of dying from CCRCC compared to patients with tumours without MVI at surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In univariate analysis we did find a survival advantage in favour of incidentally detected RCC compared with symptomatic RCC. However, in keeping with the findings of Ishimura et al [ 20 ] and Gudbjartsson et al [ 21 ], the independent prognostic significance of mode of presentation was not confirmed in multivariate analysis. In agreement with other studies, [ 4 , 22 ] we found that elevated ESR at presentation was associated with more aggressive disease and poorer outcome for both clear cell and papillary RCC (data not shown).…”
Section: Discussionsupporting
confidence: 58%
“…The symptoms of RCC at presentation have been associated with poor outcome [ 3 , 18 , 20 ]. In univariate analysis we did find a survival advantage in favour of incidentally detected RCC compared with symptomatic RCC.…”
Section: Discussionmentioning
confidence: 99%